Hubungan Spiritual Well-Being dan Kecerdasan Emosi pada Sikap Toleransi Bagi Remaja - Raja Oloan Tumanggor; Heni Mularsih (Universitas Islam Tribakti Lirboyo Kediri, 2020)
This study analyzes the relationship between spiritual well-being and emotional intelligence to tolerance for adolescents. Spiritual well-being is the affirmation of life concerning, oneself, others, the environment, and God. This relation can be developed into four interconnected domains of human existence concerning spiritual well-being; oneself, community, environment, and God. Emotional intelligence is one of the keys to success in life. So, people are aware of themselves and others, have motivation and optimism. The study took data from 1113 adolescents from five provinces (DKI, West Java, Lampung, North Sumatra, and Central Java), aims to find out the relationship between spiritual well-being and emotional intelligence on tolerance. From the analysis of data using correlation and regression found that spiritual well-being is related to tolerance (r = 0.844 (**), p = 000 <0.001), and spiritual well-being affects the attitude of tolerance (r2 = .699, t = 30 896, p <.001). Likewise emotional intelligence is related to tolerance for adolescents (r = 0.844 (**), p = 000 <0.001) and emotional intelligence influences tolerance (r2 = .712, t = - 5102, p <.001). The higher level of spiritual well-being and emotional intelligence, the better the tolerance attitude of adolescents.